2015
DOI: 10.18805/ijar.6709
|View full text |Cite
|
Sign up to set email alerts
|

Study on genetic variation of Short Tandem Repeats (STR) markers and their association with Somatic Cell Scores (SCS) in crossbred cows

Abstract: India is the highest milk producer of the world and crossbreeding to augment genetic potential of native breeds, has played an important role to achieve this feat. The present study with five microsatellite DNA loci BM1818, BM1443, BM1905, BM1258 and MB026 associated with Somatic Cell Score (SCS) and milk production, was aimed at finding variation in 76 crossbred cows. PCR amplified products were resolved on MetaPhore ® agrose. The number of alleles for BM1443, BM1905, BM1258 and MB026 were found to be 7 each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…On the same line with the help of PCR-SSCP, Gupta et al . [ 55 ] reported a non-synonymous SNP in exon two of CD14 gene and out of three genotype observed BB genotype was found to be more susceptible to mastitis.…”
Section: Immuno-pathogenesismentioning
confidence: 99%
“…On the same line with the help of PCR-SSCP, Gupta et al . [ 55 ] reported a non-synonymous SNP in exon two of CD14 gene and out of three genotype observed BB genotype was found to be more susceptible to mastitis.…”
Section: Immuno-pathogenesismentioning
confidence: 99%
“…Based on earlier researches on microsatellite relationships with mastitis in cows (Hai-Guo et al, 2003;Chu et al, 2005;Gupta et al, 2016), three microsatellites (BM1258, BM1443 and BM1818) were used in this study. Primers sequences used according to cattle genome linkage map.…”
Section: Microsatellite Analysismentioning
confidence: 99%
“…Comparison of individual 18 genotypes of these three microsatellite markers were observed in Table (4 Chu et al (2005) studied the genetic variation of seven microsatellite loci in Beijing Holstein cows which were closely linked to Somatic Cell Score (SCS) and found a significant association with the SCS. Also, Gupta et al (2016) analyzed the association between five microsatellite loci and SCS in 76 Indian crossbred cows. They reported that BM1818 marker not associated with SCS in studied population.…”
Section: Effect Of Genotypes At Microsatellite Loci On Mastitis Incidencementioning
confidence: 99%
“…Microsatellites are employed in animals to assess genetic variance within breeds (Kunene et al, 2014). There is also a link between the genetic marker DIK20 and mastitis, as it is a sign of the presence of mastitis in dairy cattle (Gupta et al, 2016). Ajafar et al(2022) reviewed the association of bone morphogenetic protein 15 and growth differentiation factor 9 with litter size in livestock, indicating the potential of these genetic markers in improving fertility and productivity traits in livestock, suggesting that genetic polymorphisms related to fertility traits may have implications for overall productivity in sheep and goats.…”
Section: Introductionmentioning
confidence: 99%